2006
DOI: 10.1097/01.rlu.0000246855.80027.b7
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Periareolar Intradermal Tc-99m Tin Colloid and Peritumoral Intraparenchymal Isosulfan Blue Dye Injections for Determination of the Sentinel Lymph Node

Abstract: According to the results of our study, we conclude that perioareolar intradermal injection of Tc-99m tin colloid combined with peritumoral intraparenchymal injection of blue dye is an accurate and easy method of locating the sentinel node with very high detection rates. It is recommended that the combination of all methods such as lymphoscintigraphy, blue dye, and gamma probe application will increase the success rate of SLN detection in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
16
0
2
Order By: Relevance
“…The authors consequently adapted the subareolar injection technique, moving the radioactive injection away from the axilla, where most draining nodes are supposed to be located [14]. Argon et al [29] conclude that periareolar intradermal injection of radiocolloid combined with peritumoral intraparenchymal injection of blue dye is an accurate and easy method of locating SLN with very high detection rates but with low visualisation rate of the internal mammary nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors consequently adapted the subareolar injection technique, moving the radioactive injection away from the axilla, where most draining nodes are supposed to be located [14]. Argon et al [29] conclude that periareolar intradermal injection of radiocolloid combined with peritumoral intraparenchymal injection of blue dye is an accurate and easy method of locating SLN with very high detection rates but with low visualisation rate of the internal mammary nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal method of SLN identifi cation remains controversial. SLN detection is more successful when using both periareolar intradermal injection of Tc-99m sulfur colloid and subareolar injection of blue dye techniques (6). Obtaining a careful tattoo history and physical examination are valuable in the evaluation of any patient undergoing work-up for breast cancer (7).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that both deep and superficial injection approaches are valid techniques and often complementary; combinations of injection techniques (either peritumoral and subareolar/periareolar injections [33] or subdermal/ peritumoral injection [34]) may improve detection accuracy and decrease false-negative rates (FNR). This is supported by the results from Suami et al's [35] human cadaver study of breast lymphatic anatomy which showed that although the majority of superficial lymph vessels of the breast drain to only one sentinel node some show alternative lymphatic drainage.…”
Section: Methods Of Inoculationmentioning
confidence: 99%